Repetition, Identity, and Rhythm in Wittgenstein - Arielli, Emanuele (Scenari, 2022)
“I myself still find my way of philosophizing new, it keeps striking me so afresh, that is why I have to repeat myself so often. It will have become part of the flesh and blood of a new generation and it will find the repetitions boring” (Culture and Value, 1929). Wittgenstein’s style is well known for its recursive– according to some interpreter, even obsessive-compulsive – quality. The style mirrors recurring ideas, such as “Concepts are not for use on a single occasion” (Zettel, 568), and “lt is not possible that there should have been only one occasion on which someone obeyed a rule” (Philosophical Investigations, 199). This essay’s aim is to show how the notion of repetition (Wiederholung) plays a significant role in the evolution of Wittgenstein’s thought. It is the manifestation of a philosophical praxis, and although it remains in the background, it is a constant presence in his production, placing itself at the side of his best known concepts. The paper will reconstruct the path of this notion through Wittgenstein’s different phases: from the remarks developed around the time of the Tractatus, to his mathematical constructivism, to the later analyses around rule following and the principles of linguistic practices. In conclusion, it will be shown how the notion of repetition in Wittgenstein is a salient point of contact between theoretical issues, philosophical method and style of thought.